Differences in the use of surface water resources by desert birds are revealed using isotopic tracers. (18th February 2019) - Smit, Ben; Woodborne, Stephan; Wolf, Blair O; McKechnie, Andrew E
Abstract: The scarcity of free-standing water sources is a key determinant of animal and plant community structure in arid environments, and an understanding of the extent to which particular species use surface water is vital for modeling the effects of climate change on desert avifauna. We investigated interspecific variation in the use of artificial water sources among birds in the Kalahari Desert, South Africa, by (i) observations at waterholes and (ii) tracing spatial water-use patterns during summer by isotopically labeled water sources and blood sampling. More than 50% of the avian community (primarily insectivores and omnivores) were not observed to drink. The majority (53%) of species drinking at waterholes were granivorous, and their use of surface water was best predicted by their relative abundance in the community. Species representing the remaining dietary guilds drank significantly more on hot days. Blood samples revealed that only 11 of 42 species (mostly granivores and a few omnivores) showed evidence of drinking at a waterhole with enriched deuterium values; on average, in the latter birds, water from the enriched waterhole accounted for 38% of their body water pool. These findings illustrate that 2 methods employed in this study provide different, but complementary data on the relative importance of a water source for an avian community. Although our results suggest that most avian species are independent of surface water, drinking patterns on the hottest days during our study period suggest that free-standing water might become more important for some of the non-drinking species under hotter climatic conditions.